Mediterranean Region - Pattichis, George (2010)
This book provides for the first time a Europe-wide overview on the state of the art of management of recreation and nature tourism in forests. It describes the current situation and conflicts in the different regions of Europe and provides solutions illustrated by good practise examples. It addresses traditions, differences and similarities in European forests as well as new tasks, goals and strategies. The final discussion provides a profound insight into future trends regarding forest recreation and nature based tourism. The Mediterranean countries participating in the COST Action E33 are: Cyprus, Greece, Croatia, Portugal, Italy, Serbia and Bosnia-Herzegovina (Fig. 5.1). Geographically, these countries are distributed from the eastern Mediterranean area to the coasts of the Atlantic Ocean. Parts of France, which is treated as one of the central European countries has also parts with Mediterranean character and similar features to the other countries discussed in this chapter. Spain was not part of the Cost Action, so that there is no data available.